PERTUMBUHAN DAN HASIL PRODUKSI MIANA (Coleus scutellarioides L.) PADA PERBEDAAN PUPUK ORGANIK - Widyawati, Titis Dwi; Miska, Moh. Ega Elman; Kurniasih, Ratih (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2024)
The miana plant is an ornamental plant that has potential as a medicinal ingredient. The part of the miana plant that is used as an ornamental or medicinal plant is the leaves. Efforts to increase the growth and yield of miana plants include fertilization. This research aims to analyze the effect of different organic fertilizers on the growth and yield of miana through the application of automated drip irrigation technology. The design used in this research was a single-factor Randomized Complete Group Design, namely organic fertilizer with five levels and five replications each. The treatment levels in this study were without fertilizer (P0), cow manure (P1), goat manure (P2), chicken manure (P3), guano fertilizer (P4), and quail manure (P5). The results of the research show that differences in organic fertilizer affect miana growth through the application of automated drip irrigation technology which can be seen in the parameters of plant height, number of leaves, and number of branches. Cow manure gave the highest average value and was able to increase miana growth most dominantly at the start to the end of the observation week compared to other treatments. Meanwhile, the parameters include leaf area, stem dry weight, leaf dry weight, total biomass, and total flavonoids. Goat manure gave the highest average value and increased miana yield in the leaf area, stem dry weight, and total biomass parameters, while cow manure gave the highest average value and increased miana yield in the leaf dry weight parameter. Apart from that, quail manure gave the highest average value and increased the yield of miana on the total flavonoid parameter.